2021
DOI: 10.7759/cureus.15279
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Magnesium Level With Duration and Severity of Type 2 Diabetes

Abstract: Introduction: Type 2 diabetes mellitus can give rise to several complications in the body, including electrolyte imbalance. In this study, we aim to find the association of hypomagnesemia with the duration and severity of diabetes. Understanding the association between magnesium and diabetes may assist in the early detection of hypomagnesemia and help manage the complications associated with electrolyte imbalance. Methods: This cross-sectional study was conducted in the internal medicine department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Increasing data reveal that the prevalence of hypomagnesemia is high in patients with diabetes, although it varies according to study design and population characteristics, and hypomagnesemia is mostly associated with advanced age, diabetes duration, diabetes severity, treatment characteristics, and diabetic micro-and macrovascular complications. [8][9][10] For example, in an observational cohort study including 929 patients with type 2 diabetes treated in primary care, the frequency of hypomagnesemia was found to be 9.6%, and it was shown that age, duration of diabetes, body mass index, HbA1c, metformin, sulfonylurea, and DPP-4 inhibitor use were negatively associated with magnesium concentration. 4 Similar to our study, in an observational study conducted on outpatients with type 2 diabetes, the frequency of hypomagnesemia was found to be 12.9%, and it was stated that hypomagnesemia was associated with poor glycemic control and contributed to the development and progression of micro-and Second; The reason is that the cases using proton pump inhibitors were found to be significantly higher both in the group with diabetes than in the nondiabetic group and in individuals with diabetes and hypomagnesemia compared to those with normal magnesium.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Increasing data reveal that the prevalence of hypomagnesemia is high in patients with diabetes, although it varies according to study design and population characteristics, and hypomagnesemia is mostly associated with advanced age, diabetes duration, diabetes severity, treatment characteristics, and diabetic micro-and macrovascular complications. [8][9][10] For example, in an observational cohort study including 929 patients with type 2 diabetes treated in primary care, the frequency of hypomagnesemia was found to be 9.6%, and it was shown that age, duration of diabetes, body mass index, HbA1c, metformin, sulfonylurea, and DPP-4 inhibitor use were negatively associated with magnesium concentration. 4 Similar to our study, in an observational study conducted on outpatients with type 2 diabetes, the frequency of hypomagnesemia was found to be 12.9%, and it was stated that hypomagnesemia was associated with poor glycemic control and contributed to the development and progression of micro-and Second; The reason is that the cases using proton pump inhibitors were found to be significantly higher both in the group with diabetes than in the nondiabetic group and in individuals with diabetes and hypomagnesemia compared to those with normal magnesium.…”
Section: Discussion Discussionmentioning
confidence: 99%
“… 31 While our finding was lower than Pakistan (57.3%), Nepal (50%), and India (44%). 9 , 32 , 33 Variation in the targeted groups may be related to dietary habits, the severity of DM, and the heterogeneity of the selected patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were comparable with a study done in Pakistan and India. 32 , 47 Due to insulin’s role in regulating Mg 2+ reabsorption in the kidney through the TRPM 6 channel. Insulin resistance or insulin deficit decreased renal magnesium absorption by blocking the TRPM 6 channel, which led to urine magnesium wasting.…”
Section: Discussionmentioning
confidence: 99%
“…Pratyush Kumar (Ấn Độ) báo cáo tỉ lệ này đến 44 % có lẽ do khác biệt cỡ mẫu và một số đặc điểm như HbA1C và BMI đều cao hơn. Trên 300 BNĐTĐ típ 2 Ruchir Paladiya ghi nhận nồng độ Mg máu trung bình khá thấp (0,66mmol/L) và tỉ lệ hạ Mg 57,3% nhiều gấp hai lần kết quả của chúng tôi [7] do tiêu chuẩn chọn bệnh của họ ít chặt chẽ, không loại người có uống thuốc hoặc có bệnh lý làm hạ Mg máu.…”
Section: Bàn Luậnunclassified